The construct of identity in Hellenistic Judaism: essays on early Jewish literature and history - Gruen, Erich S. (Deuterocanonical and cognate literature studies, 2016)
This volume assembles twenty-three essays by Erich S. Gruen, who has written extensively on the literature and history of early Judaism and the experience of the Jews in the Greco-Roman world. Twenty-two of the articles have previously been published, and one new one was composed for the volume. Erich S. Gruen, University of California, Berkeley, CA, USA.